Data and Applications Security and Privacy XXVII 27th Annual IFIP WG 11.3 Conference, DBSec 2013, Newark, NJ, USA, July 15-17, 2013. Proceedings - Wang, Lingyu; Shafiq, Basit; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 27th IFIP WG 11.3 International Conference on Data and Applications Security and Privacy, DBSec 2013, held in Newark, NJ, USA in July 2013. The 16 revised full and 6 short papers presented were carefully reviewed and selected from 45 submissions. The papers are organized in topical sections on privacy, access control, cloud computing, data outsourcing, and mobile computing.
Privacy -- Access control -- Cloud computing -- Data outsourcing -- Mobile computing.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Data mining; Information Systems; Computer Science; Systems and Data Security; Computer Communication Networks; Management of Computing and Information Systems; Data Encryption; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery